Principles of plant genetics and breeding - Acquaah, George (Wiley-Blackwell, 2012)
To respond to the increasing need to feed the world's population as well as an ever greater demand for a balanced and healthy diet there is a continuing need to produce improved new cultivars or varieties of plants, particularly crop plants